Cerebellar Syndromes: A Medical Student Guide - Claudia K. Sellers; Suvankar Pal (University Library System, University of Pittsburgh, 2013)
The cerebellum is central to normal motor function and co-ordination, and can be frequently affected in a number of common disease processes. However, medical student teaching relating to cerebellar anatomy and pathology is lacking, leaving many graduates with a significant knowledge gap. Junior doctors need to be able to recognize 'cerebellar syndromes' on presentation to hospitals, and to identify and manage reversible causes rapidly and effectively. After review of relevant literature, a simple approach to the functional anatomy and practical classifications of common cerebellar pathology is presented here, with a focus on symptoms, signs and examination techniques essential to medical school final exams.